Development in Tear Film Osmolarity Assessments: A Review - Fagehi, Raied (Nepalese Journal of Ophthalmology, 2021)
The aim of this article is to review the development in the assessment of tear film with tear osmolarity techniques. Also, to find out the average score for tear osmolarity in normal and keratoconjunctivitis sicca (KCS) patients based on the published work.The use of tear osmolarity techniques has been started about 50 years ago. Over the last years a number of researchers have investigated the human tear osmolarity. The tear osmolarity assessment techniques have two procedures. The first procedure which is old, that involves the detection of freezing point depression and vapour pressure. The second one which is more advance and known as the electronic method, that involves the use of electrical impedance technique.All techniques used to assess tear osmolarity are good, accurate, reliable and provide comparable data. Based on the published work reviewed in this article, the average tear osmolarity for normal subjects is 303.2 ± 7.0 compared to 322.7 ± 15.9 in subjects with KCS.